HEAT EXCHANGE IN BIOTECHNOLOGICAL PROCESSES - Salimov Dilmurat Tajievich,; Tojiev Sardor Dilmurodovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article describes the main aspects of modeling biotechnological processes. The kinetics of population growth depending on thermal conductivity is investigated. Physical laws determining the processes associated with heat propagation, the Fourier law and Newton's equation, which describes the surfaces of a solid and a flow, are formulated. The analysis of thermal conductivity of biotechnological processes based on a mathematical model is considered.